Audit of antibiotic utilization patterns and practice for common eye infections at the ambulatory clinic of a teaching hospital in Ghana: Findings and implications. - Israel Abebrese Sefah; Anthony Martin Quagraine; Amanj Kurdi; Steward Mudenda; Brian Godman (PLoS ONE)
Background Antimicrobial resistance (AMR) is a serious public health issue which is exacerbated by increased inappropriate use of antibiotics for common eye infections. This cross sectional survey was to assess the appropriate use of antibiotics for eye infections in an ambulatory clinic in Ghana and possible determinants. Method The medical records of all patients who sought eye care between January 2022 to December 2022 and were prescribed antibiotics were extracted from the hospital's electronic database. Descriptive, bivariate and multivariate analyses were then conducted. Results A total of 1925 patient medical records were extracted, whose median age was 40 years (IQR 26-69), and were mostly females (58.91%, n = 1134/1925). The eye condition commonly treated with antibiotics was bacteria conjunctivitis (33.51%, n = 645/1925). The most prescribed antibiotic was gentamycin (22.96%, n = 442/1925) followed by ciprofloxacin (16.78%, n = 321/1925). These were mostly topical dosage forms (82.13%, n = 1581/1925). Systemic antibiotics prescribed were mostly from the WHO 'Access' class (83.33%, n = 280/338). The appropriate choice of antibiotic prescribed was 42.44% (n = 817/1925) and this was positivity associated with age (p<0.001), number of antibiotics prescribed (p <0.001), the prescription of topical dosage forms (p <0.001), and WHO 'Access' antibiotic class (p <0.034). Conclusion The level of appropriateness of antibiotic prescriptions for eye infections was sub-optimal. Antimicrobial stewardship programs, including prescriber education on guidelines and prescription audit to address associated factors, must now be instigated in this hospital to improve future antibiotic use and prevent the rise of AMR.